Biodiesel production from the high free fatty acid âhevea brasiliensisâ and fuel properties characterization - Ahmad, J. (Trans Tech Publications Ltd, 2014)
Energy crises, depletion of fossil fuel reservoirs, environmental pollution, global warming, green house effect and starvation are becoming very serious problems in the modern world. Biodiesel is a liquid fuel which can be the best alternative for the fossil fuels. In this study, non-edible rubber seed oil (RSO) with high free fatty acid (FFA) content (45) was used for the production of biodiesel. The process comprises of two steps, in the first step acid esterification was used to reduce the FFA and in the second step base transesterification was employed to convert the treated oil into rubber seed oil methyl esters (RSOMEs). The conversion yield of biodiesel was analyzed using gas chromatography. The fuel properties were tested using the standard procedure of ASTM D6751 and EN14214. All the properties were within the ranges of the biodiesel standards. The result shows that rubber seed oil is a potential non-edible source for biodiesel production. Â© 2014 Trans Tech Publications, Switzerland.